Applying Different Analytical Methods (GC-Mass, Spectrophotometer, Atomic Absorption, and Flame Photometry for Estimation some Chemical Constituents in leaves and Stems of the Quercus coccifera plant - Aisha Ali; Adel Abdulathim; Zuhir Akrim; Nevein Abdel-Hady; Hamad Hasan (AlQalam Journal of Medical and Applied Sciences, 2026)
Some of the different analytical methods were used to estimate some of the chemical constituents in leaves and fruits of the Quercus coccifera plant, where the GC-MS was used for the determination of Fatty acids and phenolic acids. The atomic absorption spectrometry (AAS) was used for measuring the contents of metals such as Zn, Cr, and Cu. Also, the Flame photometer was used for the determination of minerals Na, K, and Ca. On the side the spectrophotometer was applied to measure the contents of phosphorus and Nitrogen The results of this study recorded that, some of phenolic acids were found in the samples including :The concentration of phenolic acids in leafs and fruits of the studied plant as following: Chlorogeneic acid (0.0115 mg/g), 3,4-Dicaffeoly guinic acid (0.129 mg/g), 3,5- Dicaffeoylquinic acid (0.309 mg/g), 4,5- Dicaffeoylquinic acid (0.0161 mg/g), 2,5-dihydroxy Benzoic acid (0.00000589 mg/g), and Galic acid (0.166mg/g). Quercus coccifera fruits: Chlorogenic acid (0.0197 mg/g), 3,4-Dicaffeoylquinic acid (0.102 mg/g), 3,5-Dicaffeoylquinic acid (0.132 mg/g), 4,5-Dicaffeoylquinic acid (0.205 mg/g), and cinnamic acid (0.00000698mg/g). Small amounts of Fatty acids were recoded and included Saturated fatty (0.081 and 0.087mg/g) and unsaturated fatty acids containing Monounsaturated fatty acids (0.047and 0.048 mg/g) in leaves and stems, respectively, and Polyunsaturated fatty acids (0.033 and 0.049mg/g) respectively. On the other side, the contents of Sodium, potassium, Calcium, Magnesium, Nitrogen, and Phosphorus in leaves were as follows: 0.3, 11.5, 1.50, 1.82, 0.69, and 2.27 ppm, whereas the contents of the same elements in fruits were as follows: 0.08, 13.5, 0.50, 1.597, 0.52, and 2.142 ppm, respectively. This study recorded small amounts of Zinc, Copper, and Chromium, and ranged between (0.147 -0.154), (0.947 -1.132) and (0.0861 -0.0898 ppm), respectively.